Looking Into Teacher’ Use of Language In Creating Student’s Involvement and Learning Opportunity In Efl Classroom - Rita Tauhida; Usman Kasim; Asnawi Muslem (Proceedings of AICS - Social Sciences, 2021)
This study aimed to investigate the teacher’s use of language in the form of interactional features in EFL classrooms. The types of interactional features based on Self Evaluation of Teacher Talk (SETT) was implemented as the framework for this study. To collect the data, 180 minutes of unfolding classroom interaction were observed and recorded using Audio-video recorder with two instruments, such as observation sheet, and field note. The data were analyzed by using Conversation Analysis (CA). Among 14 types of interactional features suggested in SETT, 11 interactional features were found in this study. Eight of them were used to facilitate students’ learning involvement, while three hindered the students from the involvement and learning opportunity.Keywords: Interactional Features, Students’ involvement, and Learning Opportunity.